Security evaluation for graphical password - Arash, Habibi Lashkari (2011)
Nowadays, user authentication is one of the important topics in information security. Text-based strong password schemes could provide with certain degree of security. However, the fact that strong passwords being difficult to memorize often leads their owners to write them down on papers or even save them in a computer file. Graphical Password or Graphical user authentication (GUA) has been proposed as a possible alternative solution to text-based authentication, motivated particularly by the fact that humans can remember images better than text. All of Graphical Password algorithms have two different aspects which are usability and security. This paper focuses on security aspects of algorithms that most of researchers work on this part and try to define security features and attributes. Unfortunately, till now there isn’t a complete evaluation criterion for graphical password security. At first, this paper tries to study on most of GUA algorithm. Then, collects the major security attributes in GUA and proposed an evaluation criterion.